Faut-il réformer la Cour suprême du Canada ? - Grandpré, Louis-Philippe de (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The author deals with the question of the Supreme Court's entire jurisdiction over all subject matters. Is the amount of work, especially with the arrival of the Charter of Rights and Freedoms, too much for the Court to handle ? He also questions the number of judges, their nomination process, the inequity of their remuneration and the problems inherent in a dual judicial system. The thrust of the article is that it is not the Supreme Court that is in need of reform, but rather the attitude that the government has towards it.